Property law - Smith, Roger J. (Roger John), 1948- (LLAS Longman law series, 2020)
"Understand and evaluate core subject principles Property Law (Longman Law series), 10th Edition by Roger J. Smith is an indispensable guide to all aspects of this compulsory subject of property law. It combines clear and engaging explanations of core property law principles with in-depth analysis of key theoretical concepts enabling you to both understand and evaluate modern land law doctrine. Its comprehensive coverage and scholarly nature also make it accessible to both undergraduates and those pursuing more advanced study. The tenth edition has been fully updated with all significant legal developments in the area of property law, including: Regency Villas Title Ltd v Diamond Resorts (Europe) Ltd on recreational easements; Marr v Collie, relating to the scope of Stack v Dowden; NRAM Ltd v Evans and Antoine v Barclays Bank UK plc, which elucidate the meaning of 'mistake' for rectification of registered titles; The Homes (Fitness for Human Habitation) Act 2018 on obligations of landlords; and A Law Commission Report on updating land registration. For additional web updates accompanying this text, please visit go.pearson.com/uk/legalupdates. This edition is also available as an Enhanced ebook to enrich your studying experience. It has features like: self assessment questions with dedicated feedback to help gauge your progress, deep links to key case reports, statutes & other sources of interest that provide access a wealth of wider reading, end of the chapter quiz that gives further opportunity to consolidate understanding and prepare for exams"--